The potential use of gaming pedagogy to teach mathematics : case studies in Miri, Sarawak, Malaysia - Yong, Su Ting (2017)
This research explores how mathematics pedagogy can be improved by looking at how children are engaged in computer games. Two approaches were considered: (a) the use of computer games, either educational or commercial off-the-shelf (COTS) games, and (b) the use of embodied learning principles of computer games. The feasibility of these approaches was explored by examining the perceptions of students, mathematics teachers and parents along four major themes - mathematics education, technological experience, gaming experience and the use of computer games to learn mathematics. A mixed methods approach was employed in which qualitative interviews [six teachers, eight students and eight parents] and quantitative surveys [total students, n=175] were administered concurrently at two government secondary schools in Miri, Sarawak, Malaysia. Both quantitative and qualitative data were analysed independently and combined in the final interpretation to provide a holistic and consolidated finding.